Effects of repetitive practice of motor tasks on somatosensory gating - Akaiwa, Mayu; Matsuda, Yuya; Saito, Hidekazu; Shibata, Eriko; Sasaki, Takeshi; Sugawara, Kazuhiro (Frontiers in Human Neuroscience, 2023)
Electrostimulation-induced sensory information of a peripheral nerve supplying the contracting muscle is inhibited and the somatosensory evoked potential (SEP) amplitude is decreased during voluntary muscle contraction. This phenomenon is called “gating.” We reported that participants with good motor skills indicated strong suppression of somatosensory information. The present study investigated the effects of motor performance improvement following repetitive practice on the SEP amplitude. The ball rotation task (BR task) was practiced by 15 healthy participants repetitively. SEPs were recorded before (pre) and after (post) repetitive practice. The BR task performance was significantly improved and the required muscle activation to perform the task was significantly reduced after the repetitive practice. The degree of gating was not significant between pre and post for the SEP amplitude. A significant correlation was found between changes in SEP amplitude from pre to post and performance improvement. Therefore, our results suggest that repetitive practice does not change the degree of gating but changes the mechanism of gating. Furthermore, they indicate that suppression of the somatosensory area is important for improving task performance.